A Decision Support System for Priority Calculation of Travel Routes using Analytical Hierarchy Process - Izha, Rahadian M; Ramadhani, Yogi (International Journal for Applied Information Management, 2023)
Currently, selecting a route to reach a specific destination has become more convenient due to map and navigation services such as Google Maps, Apple Maps, Bing Maps, OpenStreetMap, and many more. These services provide users with the most efficient routes using their own algorithms. However, we believe that users would obtain more convincing results if they could choose a route based on their own criteria. This paper proposes a method for selecting a route using the Analytical Hierarchy Process (AHP). AHP allows users to choose criteria, whether subjective or objective, to compare values and calculate priorities, resulting in more convincing results for users. By using AHP, users can determine the most suitable route according to their preferences and needs, providing a more personalized and satisfactory experience. This method could be expanded in the future by integrating machine learning algorithms and real-time traffic data to further improve the accuracy of the selected route.